Extraction and Identification of New Taxoids from the Moroccan Yew - Chakchak, Hind; Zineddine, Hamid (Asian Journal of Chemistry, 2013)
The needless of the Moroccan yew (Taxus baccata) afforded a new taxoids 19-debenzoyl-19-acetyltaxinine 1 and the 5-cinnamoylbrevifoliol (=13-deacetyltaxuspine) 2. The different fractions of methanolic extract were separed by high performance liquid chromatography. Both compounds 1 and 2 were identified by gas chromatography-mass spectrometry.